Pengaruh Penambahan Prebiotik Inulin dan Fruktooligosakarida (FOS) terhadap Pertumbuhan Probiotik Bifidobacterium sp. Bb2E - Azma Nurizqi Isnasari; Dyah Fitri Kusharyati; Oedjijono Oedjijono (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
Human health is very closely related to the condition of the human digestive tract since the beginning of life. The diversity of microorganisms found in the human digestive tract is very diverse, consisting of 300-500 different species of bacteria to increase the working power of nutrition. Prebiotics such as inulin and FOS and probiotics such as Bifidobacteria are aspects that can be added for the increase of nutrition. Optimal bacterial growth can be seen in the bacterial growth curve. The research problems were how the effect of prebiotic inulin and FOS on the growth of Bifidobacterium sp. Bb2E, the amount of incubation time needed to support the growth of Bifidobacterium sp. Bb2E, and how the interaction between prebiotic types and incubation times on the growth of Bifidobacterium sp. BB2E. The purposes of this study were to study the effect of prebiotic inulin and FOS on the growth of Bifidobacterium sp. Bb2E, to know the optimal incubation time of Bifidobacterium sp. Bb2E, and to know the interaction between prebiotic types and incubation times on the growth of Bifidobacterium sp. BB2E. This research was conducted using a completely randomized design (CRD) with factorial patterns. The main parameter measured was the population of Bifidobacterium sp. Bb2E, and the additional parameters measured were the pH level and the value of lactic acid titrated. The independent variable discussed in this study is prebiotic estimation on the medium, while the dependent variable considered is the population of Bifidobacterium sp. BB2E. The results of this study showed that the addition of inulin and fructooligosaccharide prebiotic at different incubation times had a significant effect on the growth of Bifidobacterium sp. Bb2E. The best treatment was a combination of inulin + FOS at incubation time of 18 hours with an optical density value was 1,794 and a total population density was 2,44x1010 CFU/mL.